Exigibilidad de la cláusula penal en época de crisis sanitaria - Alcántara Francia, Olga Alejandra (2020)
This article presents a reflection on the future of the penal clause, its functions, its usefulness and its validity. With the help of descriptive, hermeneutic-legal and comparative methods, we carry out a review of national and foreign regulations, about the intangibility of the contract, the moderating power of the judges and the legislative intervention in the reduction of the penal clause, as a measure temporary as a result of the health crisis.